Funções quadráticas : ensino e aplicações - Almeida, Ernesto Araújo de (2020)
The difficulty that students face in the first year of high school is related to the study of quadratic functions, in solving quadratic equations and building their graph, because, generally, the first contact with non-linear curves happens from the construction of the parable, the point of signifying the success or failure of students in subjects related to Exact Sciences, such as Mathematics and Physics. The objective of this dissertation is to contribute to the teaching and learning of quadratic functions in the final series of basic education and, mainly, in the initial series of high school, and to guide pedagogical practice through its applications, such as in Physics and Economics, providing correlations with the real world without ignoring digital technologies, such as the PhET simulator and the GeoGebra application, whose appropriate and interactive uses can facilitate the understanding of concepts and properties, in addition to functioning as a useful tool in the abstraction process, allowing a more transparent view of the subject under study.